Analysis of Conventional Type Fire Alarm System in PKU Muhammadiyah Gombong Hospital Building - Mellysa Adelia Eka Putri; Dyah Widi Astin Intansari (International journal of technology and education research, 2026)
Abstract The reliability of active fire protection systems is an important aspect for hospital buildings because it accommodates physically limited (immobile) patients and sensitive medical equipment. This study evaluates the spatial effectiveness, operational reliability, and feasibility of conventional fire alarm installations in Building J (Al Mukmin Isolation) and Building G (Chemotherapy, Radiotherapy, and LINAC) of PKU Muhammadiyah Gombong Hospital based on SNI 03-3985-2000 regulations and Public Works Regulation No. 26/PRT/M/2008. Using a comparative quantitative descriptive approach, the detector distribution over an area of ​​6,210 m² is very effective macro with an effectiveness index of 123% (130 actual units compared to 106 units of minimum requirements). However, at a micro level, an anomaly was identified in the form of a deficit of 6 units of Rate of Rise (ROR) type heat detectors in critical medical areas, which expanded the average actual protection coverage of heat detectors to 88 m² (exceeding the maximum SNI threshold of 46 m²). Although the system's feasibility level is in the